Smooth output feedback stabilization for a class of high-order switched nonlinear systems. (August 2018) - Lin, Xiangze; Li, Xueling; Chen, Chih-Chiang; Li, Shihua
Abstract: In this paper, the problem of global stabilization via smooth output feedback, for a class of high-order switched nonlinear systems with subsystems whose Jacobian linearization neither controllable nor observable, is addressed. By virtue of adding a power integrator approach, a common Lyapunov function is found and state stabilizing feedback laws are designed simultaneously. Reduced-order observers for the switched nonlinear systems are constructed to estimate the unmeasurable states. A machinery is developed to make the observer gains assignment in an iterative way possible. Coupling the state feedback controllers with the developing nonlinear observers, global asymptotical stabilization of the switched nonlinear system under arbitrary switchings is achieved by the output feedback control. An example is employed to verify the efficiency of the proposed method.